Contributions of Arab and Muslim Thinkers to the Development of Logic and the Dilemma of its Current State in the Arab World - Al-Khatib, Tahani Salah; AlAhmad, Ahmad Abdalla (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to highlight the impact of Islamic philosophers on the development of logic by attempting to answer the following questions: First, did Islamic philosophers merely reframe Aristotelian logic, or did they create new methods that enriched the concepts and issues of logic? Second, has the interest in the science of logic declined today in the Arab world compared to the golden age of Arab-Islamic civilization? Methods: This study employed the analytical method and the comparative method, as both are suitable for the study's subject. Results: The study found two main points. First, early Islamic philosophers did not merely transmit Aristotelian logic; they creatively refined, developed, and re-employed it, highlighting its significance in Arab-Islamic civilization. Second, today's Arab world shows declining interest in logic, limiting its application to mathematical logic in specific fields, which has diminished its broader importance in developing thinking and problem-solving skills. Conclusions: Early Arab and Muslim philosophers approached logic diversely—some criticized and offered alternatives to Aristotelian logic, others refined and developed it, and some integrated it with other sciences. This contrasted with the current marginalization of logic in the Arab world. The study calls for renewed focus on logic across all educational levels and disciplines in the Arab world.